+0  
 
0
43
1
avatar

-8y(7y-2)= y2+16y

Guest Mar 7, 2017
Sort: 

1+0 Answers

 #1
avatar
+5

-8y(7y-2)= y^2+16y . Did you make this one up?

 

Solve for y:
-8 y (7 y - 2) = y^2 + 16 y

Expand out terms of the left hand side:
16 y - 56 y^2 = y^2 + 16 y

Subtract y^2 + 16 y from both sides:
-57 y^2 = 0

Divide both sides by -57:
y^2 = 0

Take the square root of both sides:
Answer: |y = 0

Guest Mar 7, 2017

28 Online Users

avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details